A single diffractive optical element implementing spectrum-splitting and beam-concentration functions simultaneously with high diffraction efficiency - 叶佳声 王进泽 黄庆礼 董碧珍 张岩 杨国桢 (Chinese physics B, 2013)
In this paper,a novel method is proposed and employed to design a single diffractive optical element（DOE） for implementing spectrum-splitting and beam-concentration（SSBC） functions simultaneously.We develop an optimization algorithm,through which the SSBC DOE can be optimized within an arbitrary thickness range according to the limitations of modern photolithography technology.Theoretical simulation results reveal that the designed SSBC DOE has a high optical focusing efficiency.It is expected that the designed SSBC DOE should have practical applications in high-efficiency solar cell systems.